Solving fuzzy-facilities layout problem using genetic algorithm - Purnomo, Muhammad Ridwan Andi (2013)
Facilities layout is one of the important factor to be considered for efficiency and effectiveness of the production system. A good departments layout leads to minimum material flow cost. In departments layout analysis, there are several important factors that need to be considered. The most important factor in such analysis is activity relationship among departments. Most of the previous researches assume that the activity relationship is a fixed matrix to be used as input of optimisation analysis. This assumption is not relevant with real production system condition, which has dynamic situation. This study proposes a fuzzy logic to model activity relationship among departments. The output of the fuzzy logic is closeness rating among departments. There are 3 inputs considered in the fuzzy modelling namely material flow, frequency of equipment movement and number of operator. Further, the obtained matrix is used for layout optimisation that conducted using Genetic Algorithm (GA). Comparison study among optimised and initial layout has also carried out and it shows that the optimised layout has 8.6% of improvement.